PERBANDINGAN SIFAT KIMIA DAN KESUBURAN FISIK TANAH PADA KONDISI TEMPAT TUMBUH ALAMI DAN BUDIDAYA TALAS BENENG (Xanthosoma undipes K.Koch) DI KAWASAN GUNUNG KARANG KAMPUNG JUHUT KABUPATEN PANDEGLANG PROVINSI BANTEN - AM Kartina; Hermita Nuniek; Andi Apriany Fatmawaty (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
A research was aimed to know differences of fertility rates and physical chemistry on the type of talas beneng that grow wild and cultivated. This research was conducted from March until October 2015 in the village of Juhut, Pandeglang District, Banten Province. The research used survey and experiment methods. The results showed that the chemical characteristics of the soil on site conditions of wild talas beneng were: soil acidity was slightly sour, C-organic was low, total phosphorus was low to moderate, and potassium total was moderate. The physical properties and genesis of land had a silty loam texture. The soil structure had glob rounded, moist consistency was loose and without sticky. At cultivation growing conditions in the village of Juhut, Pandeglang in cultivation had status chemical properties of soil: soil acidity was neutral, C-organic content was low, total phosphorus was low to moderate, and total potassium was high. The physical properties and genesis was a silty clay loam soil, with a crumb structure, relatively moist crumbly consistency, with rather sticky.Keywords: Cultivation, Planting, Xanthosoma undipes